2013
DOI: 10.1111/bjd.12291
|View full text |Cite
|
Sign up to set email alerts
|

Skin metastases in metastatic uveal melanoma:GNAQ/GNA11mutational analysis as a valuable tool

Abstract: Knowledge about the mutational status of uveal melanomas opens the opportunity for future targeted therapies that directly interact with the mutation and its activated signal cascades. First trials in uveal melanoma have shown promising results with MEK inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Furthermore, molecular studies have been found to be useful in differentiating melanoma subtypes. Tsianakas and colleagues recently reported the usefulness of GNAQ and GNA11 mutational analysis to distinguish a skin metastasis in metastatic uveal melanoma from a primary cutaneous melanoma . Fuld et al .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, molecular studies have been found to be useful in differentiating melanoma subtypes. Tsianakas and colleagues recently reported the usefulness of GNAQ and GNA11 mutational analysis to distinguish a skin metastasis in metastatic uveal melanoma from a primary cutaneous melanoma . Fuld et al .…”
Section: Discussionmentioning
confidence: 99%
“…GNA11, the subunit of G proteins, is involved as modulators or transducers in various transmembrane signaling systems [ 22 ]. The gene mutations of GNA11 were frequently observed in human uveal melanomas, implying that it could lead to the initiation of uveal melanomas [ 23 , 24 , 25 ]. A study showed that GNA11 mutations also occurred in hepatic small vessel neoplasms [ 26 ].…”
Section: Introductionmentioning
confidence: 99%